2018
DOI: 10.1155/2018/5432751
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Has No Efficacy in Reducing the High Bone Turnover and the Risk of Spontaneous Vertebral Fractures after Denosumab Discontinuation

Abstract: At denosumab discontinuation, an antiresorptive agent is prescribed to reduce the high bone turnover, the rapid bone loss, and the risk of spontaneous vertebral fractures. We report the case of a woman treated with aromatase inhibitors and denosumab for 5 years. Raloxifene was then prescribed to prevent the rebound effect. Raloxifene was ineffective to reduce the high bone turnover and to avoid spontaneous clinical vertebral fractures. We believe that among the antiresorptive treatments, the most powerful bisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…There was no relationship between the number of Dmab injections and LS‐BMD changes (month 12 to 24) in either group of women; in the Dmab group, the correlation coefficient ( rs ) between changes in LS‐BMD and number of denosumab injections (4 to 10) was −0.155 ( p = 0.415). In the ZOL group, the respective rs was −0.002 ( p = 0.991).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…There was no relationship between the number of Dmab injections and LS‐BMD changes (month 12 to 24) in either group of women; in the Dmab group, the correlation coefficient ( rs ) between changes in LS‐BMD and number of denosumab injections (4 to 10) was −0.155 ( p = 0.415). In the ZOL group, the respective rs was −0.002 ( p = 0.991).…”
Section: Resultsmentioning
confidence: 89%
“…In the FREEDOM study and its Extension, Dmab was shown to increase BMD to such levels in a substantial number of women with postmenopausal osteoporosis that might lead in clinical practice to treatment discontinuation when the target is reached. However, the effect of Dmab, as of other antiosteoporotic medications with the exception of bisphosphonates, is rapidly reversible and may be also associated in a few patients with increased incidence of clinical vertebral fractures . A strategy to consolidate and maintain the Dmab‐induced BMD gains for longer periods of time is, therefore, desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there is controversy over the optimal timing and dosing of bisphosphonate therapy after denosumab discontinuation, although ongoing randomized controlled trials are expected to shed more light into this matter. It also remains unclear whether less potent antiresorptive medications, such as raloxifene, may be able to prevent the high bone turnover state after denosumab discontinuation . Regarding transitioning from denosumab to osteoanabolic treatment, there is evidence that switching to teriparatide leads to a high bone turnover state and a temporary but rapid decrease in BMD, especially at cortical skeletal sites .…”
Section: Pharmacologic Osteoporosis Treatmentmentioning
confidence: 99%